Modification of organic waste into multi-functional products for household needs - Marlinda, Marlinda; Nadir, Mardhiyah; Faisal, Muhammad; Syam, Muhammad Taufik; Basuki, Basuki; Amanda, Dea Prisca (Community Empowerment, 2021)
ACC (Ability, Care, Cultured) community is residents who have processed inorganic waste regularly, while organic waste has not been processed. This condition causes more organic waste to accumulate in landfills (TPS). This is due to the lack of knowledge and lack of desire for organic waste processing. The transfer of knowledge and sustainable assistance is the goal of this community service until ACC residents can independently process organic waste into multi-functional products. The methods used are training, mentoring and evaluation. The training was conducted to educate the residents in producing organic waste processing products in the form of liquid organic fertilizer (POC) and eco-enzyme solutions. After the training, the community has been able to make organic waste processing products independently.